Pengaruh Pertumbuhan Perusahaan, Umur Perusahaan dan Financial Distress terhadap Manajemen Laba - Setyaningrum, Indah; Nursita, Meta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of company growth, company age, and financial distress on earnings management listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The number of samples used in this research is 9 companies using purposive sampling technique. And the data used in this research is secondary data using the panel data regression method. And in testing panel data regression estimates, researchers used the help of Eviews 12 software. The results obtained in this study indicate that Company Growth, Company Age and Financial Distress simultaneously (F Test) have an effect on Profit Management, partially showing that the Company Growth variable (X1) has no effect on Profit Management, the Company Age variable (X2) that it partially has an effect on Earnings Management, and the Financial Distress variable (X3) shows that it partially has an effect on Earnings Management.